Combinação dos Métodos dos Elementos de Contorno e dos Elementos Finitos: aplicação a problemas de potencial - Marques, Eduardo (1986)
The present work is concerned with the development of computational procedures for numerical analysis in which it is advantageous using Boundary Elements and Finite Elements for solving potential problems. The main procedures employed so far to deal with phisical and geometrical descontinuities in Boundary Element analysis are studied. Two approaches are studied to form the complete global matrix combining the FEM and BEM: one obtainning an equivalent matrix from the Boundary Element matrices and another by the condensation of the Finite Element Matrix on the boundary nodes. It is also presented a discussion concerning some aspects of Symmetrization of the Global Matrix obtained with the BEM and the resolution of the final system of equations. Finally, comparative examples are presented aimming to check the eficiency of the procedures discussed.